Using Mg Isotopes to Estimate Natural Calcite Compositions and Precipitation Rates During the 2010 Eyjafjallajökull Eruption - Pogge von Strandmann, Philip A. E.; Olsson, Jonas; Luu, Tu-Han; Gislason, Sigurður R.; Burton, Kevin W. (Frontiers in Earth Science, 2019)
Chemical weathering of silicate rocks is a key control on the long-term climate, via drawdown of atmospheric CO2. Magnesium isotopes are increasingly being used to trace weathering, but are often complicated by several coincident fractionating processes. Here we examine Mg isotope ratios of waters stemming from beneath lava flows from the 2010 Eyjafjallajökull eruption. Travertine calcite was observed directly precipitating from these high-TDS (total dissolved solids) waters, and were also sampled. This system therefore provides the opportunity to study natural Mg isotope fractionation by calcite. Riverine 26Mg increase from -2.37‰ to +0.43‰ with flow distance, as isotopically light travertine precipitates (26Mg = -3.38 to -3.94‰). The solution Mg isotope ratios also co-vary with pH, calcite saturation indices and Sr/Ca ratios, strongly indicating that they are dominantly controlled by carbonate precipitation. Using experimental isotopic fractionation factors and the measured 26Mg values, we can predict the compositions of the precipitated travertines that are within uncertainty of the directly measured travertines. Hence, in some systems, Mg isotopes can be used to quantify carbonate precipitation.